2020
DOI: 10.1371/journal.pone.0231191
|View full text |Cite
|
Sign up to set email alerts
|

Carcass traits and meat quality of lambs fed with cactus (Opuntia fícus-indica Mill) silage and subjected to an intermittent water supply

Abstract: The present study aimed to evaluate the effect of cactus silage and an intermittent water supply for lambs on carcass traits and meat quality. Thirty-six crossbreed lambs with an initial average weight of 19.8 ± 2.1 kg and average age of 6 months were randomly assigned to a 3 × 3 factorial design comprising three addition ratios of cactus silage to the diet (0, 21, and 42% based on dry matter) and three water supply intervals (0, 24, and 48 h) with four replicates. There was no interaction (P > 0.05) between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 46 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The duration of the egg and nymph stages and egg-adult periods of D. echinocacti females, fed on cladodes cultivar "Orelha de Elefante Mexicana", Opuntia stricta [Haw.] Haw., and productivity, reduces costs and the use of labor, and enables the constant production of silage for animals confined during the dry season (Souza et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The duration of the egg and nymph stages and egg-adult periods of D. echinocacti females, fed on cladodes cultivar "Orelha de Elefante Mexicana", Opuntia stricta [Haw.] Haw., and productivity, reduces costs and the use of labor, and enables the constant production of silage for animals confined during the dry season (Souza et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The goat meat has a low lipid content with a distinct distribution in relation to other ruminant species, since the main lipid deposit in goats is in the abdominal cavity and not subcutaneous and intramuscular, as occurs in cattle and sheep [ 57 , 58 ]. These results ( Table 4 ) of the low content of lipids in the meat of kids fed on cactus agree with Mahouachi et al [ 59 ] who observed a decrease in the amount of lipids from 142 to 101 g/kg in the meat of kids fed on cactus.…”
Section: Discussionmentioning
confidence: 99%
“…Although SFAs are considered harmful to health, the potential of myristic acid to increase total serum cholesterol is 4- to 6-fold higher than that of C16:0 [ 75 ]. Moreover, not all SFAs pose a health risk: even high content of stearic acid exerts no effect on cholesterol levels, as it is poorly digested and easily desaturated to C18:1 [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proportions of MUFAs and SFAs are mainly affected by ruminal biohydrogenation, which in turn may be influenced by several factors [ 76 ]. It was found that the percentage of monounsaturated fatty acids (MUFAs) was higher in the muscles of the conventionally farmed red deer than in the case of animals from the forest feeding grounds, due to the higher concentrations of C16:1 and C17:1.…”
Section: Discussionmentioning
confidence: 99%